Colonic atresia associated with biliary atresia - Shailesh Solanki; Jai Kumar Mahajan; Palak Singhai; Suvradeep Mitra (Wolters Kluwer Medknow Publications, 2023)
Colonic atresia (CA) is an uncommon type of intestinal atresia commonly associated with other anomalies, while biliary atresia (BA) is also rare but usually an isolated anomaly. The pathogenesis for either of the anomalies is unclear. The co-occurrence of both pathologies has not been mentioned in the literature. We here discuss the management of CA with BA and the review of pertinent literature.